Modern Manager and Requirements in the Innovative Economy - Pardaev, Olim (Universitas Muhammadiyah Sidoarjo, 2019)
The article looks at the modern manager in the conditions of an innovative economy and its requirements. The requirements also include professional training of a manager, psychological qualities of a manager, general cultural level, and general academic level. The article provides a brief overview of the key aspects of the quality of a modern manager - his or her level of knowledge and the requirements for a modern manager.